STRUKTUR KOMUNITAS SERANGGA PADA TANAMAN KOPI (Coffea robusta L) DI DESA BELIMBING KECAMATAN MUARA PINANG SUMATERA SELATAN (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2016)
Research of  insect of community structure on coffe  (Coffea robusta L.) in Belimbing Village Muara Pinang  Subdistrict   Sumatera Selatan Province, conducted  September till  October  2013, to saw insect species of coffe plant, density, ferquency, importan value index and  diversity index. The research used direct survey method, and data sampling with purpossive in  transect.   The result showed gated 15 species   insects are Valanga nigricornis, Anax sp, Neoconocephalus sp, Oecopylla smaragdina, Gryllus miratus, Hydrophilus sp,  Photuris sp, Zizinia sp, Mantis sp, Phyllophaga sp,  Hypothenemus hampei,  Bactrocera conformis,  Sexava sp, Tipula sp and Polistes sp. Oecopylla smaragdina  was dominant species, with importan value index  34,94%Diversity index was medium categhory with  H’ value  2,22. Key words :   diversity, insect,  Vigna sinensis